Relationship between pathological response and molecular subtypes in locally advanced breast cancer patients receiving neoadjuvant chemotherapy. (2nd January 2023) - Değerli, Ezgi; Şentürk Öztaş, Nihan; Alkan, Gülin; Bedir, Şahin; Derin, Sümeyra; Valıkhanova, Nahıda; Saraç, Betül; Kacar, Ezgi; Demirci, Nebi Serkan; Demirelli, Hulusi Fuat; Turna, Hande
Abstract: Majority of patients with breast cancer were diagnosed with locally advanced stages of the disease (54%). This study aimed to explain the pathological response received to neoadjuvant chemotherapy (NACT) according to the molecular classification of breast cancer in patients with locally advanced tumors. One hundred and one patients with locally advanced breast cancer treated with neoadjuvant chemotherapy were analyzed. Patients were classified into five molecular subtypes based on the profile of the estrogen receptor, progesterone receptor, HER2, and Ki-67. We determined associations between complete pathological response (no invasive tumor after neoadjuvant chemotherapy) and molecular subgroups. Most patients had luminal A tumors (n: 28, 27.7%). The overall rate of complete pathological response (pCR) was 34.7% (n:35). Tumors that presented with the highest rate of pCR were pure HER2-positive, at 60% (n:6; OR, 3.2; 95% CI, 0.8–12.2). According to logistic regression analysis, the factors affecting pCR were HER2 positivity and clinically positive axilla before NACT. Luminal A tumors had a significantly lower pCR rate. (7.1%, p: 0.001). Despite the low pCR rate, Luminal A tumor had the best survival rate in the subgroups ( p < 0.001). However, there was no difference between EFS and OS according to pCR in any molecular subgroups. Pathological complete response is directly related to the subtypes of breast cancer. A high complete pathological response rate is observed in the pure HER2-positive group. However, EFS and OS were not statistically significant in patients with and without pCR.